Discovery of Renal Tuberculosis in a Partial Nephrectomy Specimen Done for Renal Tumor - Ahmed Saadi; Haroun Ayed; Abderrazak Bouzouita; Walid Kerkeni; Mohamed Cherif; Riadh M. Ben Slama; Amine Derouiche; Mohamed Chebil (Urology Case Reports, 2015)
The association of renal cancer and renal tuberculosis is uncommon. While the incidental discovery of renal cell carcinoma in a tuberculous kidney is a classical finding, the discovery of tuberculous lesions after nephrectomy for cancer is exceptional. We report the case of a female patient aged 60 who had a partial nephrectomy for a 5 cm exophytic kidney tumor. Pathological examination concluded that renal clear cell carcinoma associated with follicular caseo tuberculosis.